Penerapan Lean Thinking dalam Fabrikasi Produk Sanitari: Pendekatan Komprehensif untuk Mengurangi Pemborosan - Retnowati, Dini; Atmaja, Yuka; Khoiriyah, Nuzulia (Journal of Research and Technology, 2023)
This research focuses on integrating lean thinking into a sanitary product manufacturing company, specifically through the identification and elimination of waste. The implementation of the Lean DMAI framework (Define, Measure, Analyze, Improve) is utilized as a continuous improvement strategy to enhance efficiency and reduce waste. Various tools such as Pareto diagrams, root cause analysis, and Failure Mode and Effect Analysis (FMEA) are employed in the stages of defining, measuring, analyzing, and providing improvement recommendations. Results of the study revealed that the waste with the highest Risk Priority Number (RPN) is in the form of defects, particularly in the sub-category of body cracks. The recommended improvement actions include the installation of temperature sensors and misting equipment, along with the application of damp cloths in the lower leg area. These measures aim to slow down the body shrinkage process.